Erratum: Pyke, A.T. et al. On the Home Front: Specialized Reference Testing for Dengue in the Australasian Region. Trop. Med. Infect. Dis. 2018, 3, 75 - Alyssa T. Pyke; Wendy Gunn; Carmel Taylor; Ian M. Mackay; Jamie McMahon; Lauren Jelley; Ben Waite; Fiona May (Tropical Medicine and Infectious Disease, 2019)
The authors wish to make the following correction to Table 1 of this paper [...]